Inventarisasi Famili Asteraceae di Hutan Batu Tikar Kecamatan Luwuk Kabupaten Banggai - Nurlia, Nurlia; Karim, Wahyudin Abdul; Khaerunisa, Diana; Panigoro, Nial Setiawan (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2022)
Forests are one of the natural resources that has an important and potential role for human life, therefore it is necessary to preserve their existence as a function to support living systems. The objective of this research is to know how to make an inventory of plant species belonging to Family Asteraceae in Batu Tikar Forest, Luwuk District, Banggai Regency. This type of research is descriptive research. Researchers seek, collect, describe, and interpret research data found in the field systematically, factually, and accurately. This research was conducted in August 2020. Sampling was carried out by the exploration method, namely tracing the research area. It is Batu Tikar forest. The data obtained from the research results were then analyzed descriptively qualitatively. The results of this study found 9 species, namely Chromolaena odorata, Eclipta prostrata, Synedrella nodiflora, Ageratum Conyzoides, Tridax procumbens, Cyanthillum cinereum, Ludwigia hyssopifolia, Acmella paniculata and Bidens pilosad with a total of 39 individuals. From the research results, it can be seen that the plants of the asteraceae family belong to 9 genera, namely Chromolaena, Eclipta, Synedrella, Ageratum, Tridax, Cyanthillum, Ludwigia, Acmella and Bidens.